Association study of STAT4 polymorphisms and type 1 diabetes in Northeastern Chinese Han population. Issue 3 (30th January 2013) - Bi, C.; Li, B.; Cheng, Z.; Hu, Y.; Fang, Z.; Zhai, A.
Abstract Type 1 diabetes (T1D) is an organ‐specific, T‐cell‐mediated disease resulting from the selective destruction of pancreatic β cells. The signal transducer and activator of transcription 4 (STAT4) gene is one of the most interesting genes for the pathogenesis of autoimmune diseases, including T1D. In this study, a case–control study was conducted in a Han population in northeastern China comparing the genotypes of T1D patients to healthy controls for the presence of two single‐nucleotide polymorphisms (SNPs) in the STAT4 gene. The study population comprised of 410 T1D patients and 407 healthy individuals. Two SNPs (rs7574865 and rs3024866) of STAT4 were genotyped with Multiplex SNaPShot method. Data were analyzed with spss 13.0 to determine if a statistical association existed between these genotypes and T1D. One of the two SNPs (rs7574865) was strongly associated with T1D in Northeastern Chinese population compared to healthy controls (P < 0.05), whereas the other tested SNP (rs3024866) demonstrated no significant relationship. In conclusion, the STAT4 gene may play an important role in facilitating susceptibility to T1D in this Han Chinese population.